Carbon fibre/graphene foam/polymer composites with enhanced mechanical and thermal properties. (1st June 2016) - Zhao, Yun-Hong; Zhang, Ya-Fei; Bai, Shu-Lin; Yuan, Xiao-Wen
Abstract: The effect of carbon fibre (CF) on the mechanical and thermal properties of graphene foam (GF)/polydimethylsiloxane (PDMS) composites was investigated. The CFs with different weight percentages (2, 4, 6, 8 and 10 wt%) were thoroughly dispersed in the PDMS matrix using a high-speed shearing and stirring method and then the GF was filled with the mixture. The CF/GF/PDMS composites were characterized in terms of microstructure, mechanical and thermal properties using various testing techniques. The results reveal that the addition of CF observably improved the mechanical and thermal properties of GF/PDMS composites. For 10 wt% CF/GF/PDMS composite, the tensile strength and Young's modulus are increased by 52% and 71% respectively compared with GF/PDMS composite. In addition, its thermal conductivity reaches 0.55 Wm −1  K −1, i.e., an increase by about 41% and 162% compared to GF/PDMS composite and pure PDMS, respectively. SEM images show a strong interfacial bonding between CF and PDMS.